Krill oil: nutraceutical potential in skin health and disease - Duo, Lan; Yang, Jianzhong; Wang, Xue; Zhang, Gang; Zhao, Jiuxiang; Zou, Hong; Wang, Zhi; Li, Yu (Frontiers in Nutrition, 2024)
Krill oil (KO), extracted from the Antarctic marine crustacean Euphausia superba, is a nutrientdense substance, including rich profiles of n-3 polyunsaturated fatty acids (n-3 PUFAs), phospholipids (PLs), astaxanthin (ASX), as well as vitamins A and E, minerals, and flavonoids. As a high-quality lipid resource, KO has been widely used as a dietary supplement for its health-protective properties in recent years. KO has various benefits, including antioxidative, anti-inflammatory, metabolic regulatory, neuroprotective, and gut microbiome modulatory effects. Especially, the antioxidant and antiinflammatory effects make KO have potential in skin care applications. With increasing demands for natural skin anti-aging solutions, KO has emerged as a valuable nutraceutical in dermatology, showing potential for mitigating the effects of skin aging and enhancing overall skin health and vitality. This review provides an overview of existing studies on the beneficial effects of KO on the skin, exploring its functional roles and underlying mechanisms through which it contributes to dermatological health and disease management.